Etiopathogenesis of Basedow's disease - Leporati, P.; Groppelli, G.; Zerbini, F.; Rotondi, M.; Chiovato, L. (Nuklearmedizin - NuclearMedicine, 2015)
Basedow's disease (BD) owes its name to the German physician Karl Adolph von Basedow, who described in 1840 the clinical picture of exophthalmic toxic goitre. More than one century after the seminal paper of Karl von Basedow, the ultimate cause of BD remains to be fully elucidated. In the last years, evidence was accumulated indicating that BD is a polygenic and multifactorial disease that develops as a result of a complex interplay between genetic susceptibility and environmental and endogenous factors, which leads to the loss of immune tolerance to thyroid antigens and in particular to the TSH receptor.Our aim is to review the current knowledge on the pathogenesis of BD. To this purpose, we will firstly focus our attention on the role of genetic factors (the HLA complex, the genes encoding for thyroglobulin, the TSH receptor, CD40, CTLA-4 and PTPN22), and of environmental factors (iodine, infections, psychological stress, gender, smoking, thyroid damage, vitamin D, selenium, immune modulating agents) as possible causes of BD. Taking advantage of the experimental animal models of BD, we will then focus on the immunological mechanisms leading to the loss of tolerance in BD. The pathogenic role played by the chemokine system will be also reviewed.
Keywords: Basedow; Graves; chemokines; thyroid; autoimmunity